Implications of Single-Vessel Runoff on Long-Term Outcomes of Free Tissue Transfer for Lower Extremity Reconstruction - Huffman, Samuel S.; Bovill, John D.; Li, Karen; Spoer, Daisy L.; Berger, Lauren E.; Bekeny, Jenna C.; Akbari, Cameron M.; Fan, Kenneth L.; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2023)
Background Patients with complex lower extremity (LE) wounds and single-vessel LE runoff (1-VRO) are often considered for amputation. While more challenging, free tissue transfer (FTT) is a means for limb salvage. This study aims to demonstrate the feasibility of limb salvage with FTT in patients with 1-VRO.Methods Patients undergoing FTT by a single surgeon between 2011 and 2021 were retrospectively reviewed. Data collected included demographics, wound characteristics, vascular status, and operative details. Patients were divided into cohorts based on 1- versus 3-VRO of tibial vessel inflow. Outcomes of interest included postoperative complications such as flap necrosis, flap success, limb salvage, and ambulatory status.Results A total of 188 patients underwent FTT to LE, with 25 patients (13.3%) having 1-VRO. Patients with 1-VRO had a comparable prevalence of diabetes (56.0% vs. 50.0%, p = 0.569) and end-stage renal disease (8.0% vs. 3.7%, p = 0.319). Osteomyelitis was more common in the 1-VRO group (80.0% vs. 60.1%, p = 0.056). FTT donor sites and flap composition were similar between cohorts. At mean follow-up of 21.2 months (interquartile range 24.5:5.6, 30.1 months), limb salvage rates were similar between cohorts (84.0% vs. 91.4%, p = 0.241), with no significant differences in ambulatory status or mortality. Higher complication rates occurred in the 1-VRO cohort (48.0% vs. 21.5%, p = 0.004), of which partial flap necrosis was more prevalent in the 1-VRO group (8.0% vs. 1.2%, p = 0.029). There was no difference in flap success rates between groups (p = 0.805). More postflap angiograms were performed in the 1-VRO group (32.0% vs. 9.2%, p = 0.001), but there was no difference in need for repeat percutaneous endovascular intervention between groups.Conclusion This study demonstrates that FTT reconstruction to the LE remains a reliable reconstruction option for limb salvage in patients with single-vessel supply to the LE. Reliance on advanced perioperative management and patient optimization is effective at reducing negative outcomes.
Keywords: limb salvage; amputation; free tissue transfer; end-to-side anastomosis; vessel runoff